Pembinaan Karakter Siswa Melalui Projek Penguatan Profil Pelajar Pancasila di SMA Takhasus Al Quran Wonosobo - Izza Alfiani; Sri Haryanto; Vava Imam Agus Faisal (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
This study aims to explore the development of student character through the Pancasila Student Profile Strengthening Project at SMA Takhasus Al Quran Wonosobo. This study uses a qualitative approach with a case study method, which involves data collection through interviews, observations, and documentation. The results of the study indicate that the implementation of this project was carried out in two stages, namely the training stage and the work presentation stage, which effectively developed student character in accordance with Pancasila values. In the training stage, students are trained to work together and collaborate, while in the work presentation stage, they are given the opportunity to display work that reflects creativity and independence. In addition, this study also identified supporting factors such as adequate facilities and infrastructure and available budget, as well as inhibiting factors such as the lack of interest of some students in project activities. These findings indicate that the Pancasila Student Profile Strengthening Project is an effective strategy in shaping student character at SMA Takhasus Al Quran Wonosobo, with the hope that it can make a positive contribution to the development of character education in Indonesia.